ISO/IEC MPEG-2 Advanced Audio Coding - Herre, Jürgen; Brandenburg, Karlheinz; Quackenbush, Schuyler R.; Fielder, Louis; Akagiri, Kenzo; Fuchs, Hendrik; Dietz, Martin; Davidson, Grant A.; Oikawa, Yoshiaki; et al. (Journal of the Audio Engineering Society, 1997)
The ISO/IEC MPEG-2 advanced audio coding (AAC) system was designed to provide MPEG-2 with the best audio quality without any restrictions due to compatibility requirements. The main features of the AAC system (ISO/IEC 13818-7) are described. MPEG-2 AAC combines the coding efficiency of a high-resolution filter bank, production techniques, and Huffman coding with additional functionalities aimed to deliver very high audio quality at a variety of data rates.<br
herre_books_journals